Understanding Anxiety among Students Who Memorize the Qur'an - Naufalita, Naufalita; Sari, Ratna (Jurnal Psikologi Integratif, 2024)
Anxiety may be experienced by all groups, including students who memorize the Qur’an.  This research aims to explore the types of anxiety experienced by students who memorize the Qur'an, identify the factors that contribute to it, and examine the efforts made by supervisors to address it. The study used a qualitative approach, with data collected through observation and interviews, and analyzed using the Miles and Huberman model. The results showed that students experienced both reality-based and moral-based anxiety. Environmental factors were found to contribute to anxiety, and institutional support was found to be lacking. While the vice principal made no efforts to address anxiety among students, the tahfiz extracurricular participants used self-control, asking for help, and muroja’ah as strategies to cope. This study identifies several types of anxiety and variables that contribute to it while emphasizing the importance of institutional support in resolving mental health issues. Practical consequences of this research include the development of customized treatments for students, training for educators on identifying anxiety and establishing extensive support systems within educational institutions. Kecemasan mungkin dialami oleh semua kalangan, termasuk siswa penghafal Al-Qur’an. Penelitian ini bertujuan untuk menggali jenis-jenis kecemasan yang dialami siswa penghafal Al-Qur’an, mengidentifikasi faktor-faktor yang menyebabkannya, dan mengkaji upaya yang dilakukan guru pembimbing untuk mengatasinya. Penelitian ini menggunakan pendekatan kualitatif, dengan pengumpulan data melalui observasi dan wawancara, serta dianalisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa siswa mengalami kecemasan berbasis realitas dan berbasis moral. Faktor lingkungan ditemukan berkontribusi terhadap kecemasan, dan dukungan kelembagaan ditemukan kurang ada. Meskipun wakil kepala sekolah tidak melakukan upaya untuk mengatasi kecemasan di kalangan siswa, peserta ekstrakurikuler tahfiz menggunakan pengendalian diri, meminta bantuan, dan muroja’ah sebagai strategi untuk mengatasinya. Studi  ini mengidentifikasi beberapa jenis kecemasan dan faktor yang berkontribusi terhadapnya, sekaligus menekankan pentingnya dukungan institusional dalam menyelesaikan permasalahan kesehatan mental. Konsekuensi praktis dari penelitian ini mencakup pengembangan intervensi yang disesuaikan untuk siswa, pelatihan bagi pendidik dalam mengidentifikasi kecemasan, dan membangun sistem pendukung yang luas di lembaga pendidikan.